2016
DOI: 10.3201/eid2209.150647
|View full text |Cite
|
Sign up to set email alerts
|

PersistentBacillus cereusBacteremia in 3 Persons Who Inject Drugs, San Diego, California, USA

Abstract: Bacillus cereus is typically considered a blood culture contaminant; however, its presence in blood cultures can indicate true bacteremia. We report 4 episodes of B. cereus bacteremia in 3 persons who inject drugs. Multilocus sequence typing showed that the temporally associated infections were caused by unrelated clones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…In addition, the cellular mechanism and the interaction between different virulence factors should be further studied. Recent reports showed that the persistent B. cereus interaction with host cells is even hard to control [1,49,143], and compared to other persistent bacteria, B. cereus are more dangerous due to the high transmission and viability of their spores [69,99,144]. In sum, strong emphasis should be placed on the B. cereus in dairy products to guarantee the safety of human life in China.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the cellular mechanism and the interaction between different virulence factors should be further studied. Recent reports showed that the persistent B. cereus interaction with host cells is even hard to control [1,49,143], and compared to other persistent bacteria, B. cereus are more dangerous due to the high transmission and viability of their spores [69,99,144]. In sum, strong emphasis should be placed on the B. cereus in dairy products to guarantee the safety of human life in China.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Therefore, many other infections associated with B. cereus have been reported including meningitis, brain abscess [ 42 ], cellulitis [ 43 ], endophthalmitis [ 44 , 45 ], pneumonia [ 46 ], endocarditis [ 47 ] and osteomyelitis [ 48 ]. More seriously, persistent B. cereus strains, which are highly detrimental pathogenic bacteria against antibiotic therapies, were also found in patients in the USA [ 49 ]. Altogether, tracing the source of B. cereus, such as in dairy products, is of particular concern.…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge contributing to persistence is that spores are metabolically dormant and show reduced susceptibility to biocides, thus playing an important role in disease chronicity [ 29 ].…”
Section: Clinical Challenges Related To Sporobiota: Persistence and Rmentioning
confidence: 99%
“…A number of the bacteria that were deposited by hand dryers with and without HEPA filters and from bathroom air directly are skin flora and/or environmental organisms that are reported in the literature to potentially cause invasive human disease, including bloodstream, ocular, and peritoneal infections (33)(34)(35)(36)(37). In most of these cases, patients acquiring these diseases had a predisposition to infection, such as a permanent catheter, a defect in the immune system, underlying chronic disease (e.g., cancer), or repeated bloodborne exposure to bacteria through intravenous drug use (36,38). It is certainly clear that hand washing can reduce the risk of infections (39).…”
Section: Discussionmentioning
confidence: 99%